Unfolding the science behind policy initiatives targeting plastic pollution - Nielsen, Maria Bille; Clausen, Lauge Peter Westergaard; Cronin, Richard; Hansen, Steffen Foss; Oturai, Nikoline Garner; Syberg, Kristian (Microplastics and nanoplastics, 2023)
The intensive global plastic production, use and associated plastic pollution have caused concern for the potential risks to human health and the environment. This has led to the adoption of numerous regulatory initiatives aiming to combat plastic pollution. Despite the considerable regulatory activity in the field of plastic, it appears that there is still debate about the actual risks of plastic to humans and the environment. This raises the question of to what extent the current plastic regulation is evidence-based, a declared ambition in the European Union. Therefore, the aim of this study was to investigate to what extent key policy initiatives targeting plastic pollution are based on scientific evidence. Selection of initiatives was based on expert elicitation accounting for the opinions of persons involved in the development of the policy initiatives, and a thorough assessment of the historical development of plastic pollution regulation, with focus on their importance both with respect to regulation of plastics as well as their historical importance as drivers for societal actions on plastic pollution. We find that scientific evidence appears to be generally present in the scientific foundation for the policy initiatives analysed in this study. All the initiatives are supported by scientific articles and reports about among others plastic sources, ecological impacts of plastic production and consumption patterns. Marine litter monitoring data was found to contribute to the evidence base for 4 out of the 6 policy initiatives and thereby appears to be one of the central scientific drivers behind the societal actions on plastic pollution. Other scientific tools applied when shaping the policy initiatives include risk assessment, impact assessment and life cycle assessment. Despite the prevalent consideration and application of scientific evidence, there seems to be a broad recognition in the preparatory work of the initiatives that there is still a lot of uncertainty related to determining the harm of plastic pollution. In these cases, taking precautionary actions seems however to be justified, recalling not least the precautionary principle. As the issue of plastic pollution is complex and still subject to uncertainty, it seems important both that policy initiatives allow for flexibility and continuing adjustment to the on-going knowledge generation and that the scientific community provides the needed research to continue the science-informed policy development.